Efficacy of Sequential Capecitabine on Adjuvant Chemotherapy of Triple-Negative Breast Cancer. (28th February 2022) - Xi, Xun; Huang, Xingwei; Yuan, Huozhong; Ni, Jun; Yang, Fulan
Abstract : This paper aims to evaluate the efficacy of capecitabine as extended adjuvant treatment after anthracycline and paclitaxel combined adjuvant chemotherapy for women with early triple-negative breast cancer (TNBC). The patients with early TNBC were randomly assigned to capecitabine sequential treatment for 4 cycles and without any sequential treatment in the control group after anthracycline and paclitaxel combined adjuvant chemotherapy. The primary end point was disease-free survival (DFS). The secondary end point was overall survival (OS). One hundred patients were enrolled in this study between June 2013 and February 2015. Median age was 49 years ranging from 25 to 66 years and treatment was well tolerance. The median follow-up time after random allocation was 58 months (range: 11–62 months). There was no significant difference in DFS and OS between the two groups (hazard ratio (HR) of DFS was 0.50; 95% CI, 0.24–1.05; P = 0.066 ). Our study shows that although the addition of four cycles capecitabine after anthracycline and paclitaxel combining adjuvant chemotherapy does not improve DFS and OS, but the trend of DFS is improved. The possible reason is that the four-cycle treatment of capecitabine is not enough, and another possible reason is that the number of cases is not enough.